A Genuine Win‐Win: Resolving the "Conserve or Catch" Conflict in Marine Reserve Network Design. Issue 5 (16th November 2016) - Chollett, Iliana; Garavelli, Lysel; O'Farrell, Shay; Cherubin, Laurent; Matthews, Thomas R.; Mumby, Peter J.; Box, Stephen J.
Abstract: To support fishing communities, reserves should ensure the persistence of meta‐populations while boosting fisheries yield. However, so far their design from the onset has rarely considered both objectives simultaneously. Here we overcome this barrier in designing a network of reserves for the Caribbean spiny lobster, a species with long larval duration for which local management is considered pointless because the benefits of protection are believed to be accrued elsewhere. Our reserve design approach uses spatially explicit population models and considers ontogenetic migration, larval and adult movement. We show that yield and persistence are negatively related, but that both objectives can be maximized simultaneously during planning. Importantly, we also show that local efforts to manage spiny lobster, the most economically valuable marine resource in the Caribbean, can result in locally accrued benefits, overcoming a major barrier to investing effort in the appropriate management of this species.